Disciplining the divine : toward an (im)political theology - Fletcher, Paul (Ashgate, 2009)
Disciplining the Divine offers the first comprehensive treatment of the Social Model of the Trinity, exploring its central place within much theological discourse of the past half century, including its relation to wider cultural and political concerns. The book highlights the manner in which theologians have attempted to make the doctrine of God relevant to modern issues and outlooks and it charts the conditions that have necessitated such a reconfiguration of theological analysis. While interrogatory in tone and intent, Disciplining the Divine nevertheless provides a critical reconstruction.